2002
DOI: 10.1016/s0006-3495(02)75357-5
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond-Hetero-FRET Microscopy to Probe Protein-Protein Interactions in Live Cells

Abstract: By using a novel time- and space-correlated single-photon counting detector, we show that fluorescence resonance energy transfer (FRET) between cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP) fused to herpes simplex virus thymidine kinase (TK) monomers can be used to reveal homodimerization of TK in the nucleus and cytoplasm of live cells. However, the quantification of energy transfer was limited by the intrinsic biexponential fluorescence decay of the donor CFP (lifetimes of 1.3 +/- 0.2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
113
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 37 publications
16
113
0
1
Order By: Relevance
“…One shorter lifetime of 1.1 ns contributing for 33% and one longer lifetime of 3.7 ns contributing for 67% could be recovered. The departure of single-exponential fluorescence decay is also observed by others [18][19][20]. The presence of multiple fluorescent states is most probably due to two different conformations of ECFP in the crystal structure in which two amino acids, Tyr145 and His148, are positioned differently with respect to the fluorophore [21].…”
Section: Fluorescence Decays In Different Water-glycerol Mixturesmentioning
confidence: 73%
“…One shorter lifetime of 1.1 ns contributing for 33% and one longer lifetime of 3.7 ns contributing for 67% could be recovered. The departure of single-exponential fluorescence decay is also observed by others [18][19][20]. The presence of multiple fluorescent states is most probably due to two different conformations of ECFP in the crystal structure in which two amino acids, Tyr145 and His148, are positioned differently with respect to the fluorophore [21].…”
Section: Fluorescence Decays In Different Water-glycerol Mixturesmentioning
confidence: 73%
“…Previous time-resolved studies have also found that the fluorescence lifetime of CFP in mammalian cells is biexponential. Tramier et al [23] …”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In other photon-counting FLIM studies of FRET between CFP and YFP in cells, the extent of FRET has been described by biexponential kinetics, with two lifetimes that are different to the donor-only decays [23][24][25]. More complex kinetics were not observed.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Nous avons comparé les concentrations des protéi-nes de maturation précoces ou tardives dans les PNB. Enfin nous avons utilisé une méthode de FRET (fluorescence resonance energy transfer) fondé sur la décroissance de la durée de vie de la GFP (donneur) en présence de DsRed (accepteur) [7]. Cette analyse non invasive, est réalisée pendant l'assemblage du nucléole et mesure la distance entre les deux étiquettes fluorescentes.…”
Section: Méthodes Utiliséesunclassified